PROBLEMATIKA HUKUM DALAM PENERAPAN SANKSI PIDANA KEBIRI KIMIA BAGI PELAKU TINDAK PIDANA KEKERASAN SEKSUAL TERHADAP ANAK DI INDONESIA - Krisananda, Aldi; R, Mukhlis; Ferawati, Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Punishment against the perpetrators of sexual violence against children as stipulated in law number 17 of 2016 concerning the protection of Children, with the threat of punishment to a maximum of 20 years in prison until chemical castration punishment for perpetrators. Sexual violence against children in Indonesia continues to increase, with the passing of law number 17 of 2016 concerning child protection, which includes the punishment of medical ethics in Indonesia. In terms of human rights, chemical castration punishment is torture and humiliates human dignity, whereas in the medical code of ethich, chemical castration is a punishment that violates the doctor’s oath states that every doctor must prioritize the patient’s health.This type of research is used by using normative juridical research, namely legal research conducted by examining the standard rules that have been recorded. The focus is to examine what are the problems in the application of chemical castration criminal sanctions in Indonesia.The research results show that castration punishment does not contradict human right because castration is a detterent so that the perpetrator does not become a sexual predator. Castration is included in the theory of the purpose of punishment, this theory considers punishment as a deterrent, scares off the perpetrator both in general and specifically as well as corrects the offender so as not to commit crimes of sexual violence against children and the executor for perpetrators of sexual violence against children is carried out by the Indonesian police through the police doctor (Dokpol) and the responsibility is no longer to IDI but to the state.Keywords: Human Right, Castration Penalty, Medical.